Urban Energy Resilience in Southeast Asian Megacities: Integrating the 4A Framework and Multi-Level Governance Gaps in Jakarta, Manila, and Bangkok - Anesthesia, Annisa Priska; Imam Supriyadi; Susilo Adi Purwantoro (International Journal of Technology and Education Research, 2025)
Urban energy resilience has become a critical challenge for Southeast Asian megacities amid rapid urbanization, climate induced hazards, and increasing dependence on centralized energy systems. While existing studies predominantly emphasize technical reliability, the governance dimension of urban energy resilience remains insufficiently theorized. This study proposes a conceptual framework that integrates the four dimensions of energy security, Availability, Accessibility, Affordability, and Acceptability (4A) with the OECD’s Seven Multilevel Governance Gaps to examine how institutional structures shape urban energy resilience. This qualitative systematic literature review applies the framework to a comparative analysis of Jakarta, Manila, and Bangkok. The findings reveal contrasting resilience profiles across the three cities. Manila demonstrates low adaptive capacity due to fragmented governance and high reliance on imported energy. Jakarta exhibits dependent resilience, characterized by a stable supply but limited local autonomy under centralized energy governance. Bangkok demonstrates relatively strong resilience, supported by higher institutional capacity, although constrained by policy inertia and coordination gaps. The study concludes that urban energy resilience is driven primarily by governance performance rather than technical capacity alone. This framework provides a policy oriented analytical tool to strengthen urban energy resilience in developing countries.